PELAKSANAAN ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) PADA DITLANTAS POLDA METRO JAYA - Ferdyandaru Ardhya Pratama, Dicky; Gultom, Potler (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
An increase in the number of motorized vehicles which is directly proportional to the number of traffic violations is a common phenomenon. The Electronic Traffic Law Enforcement (ETLE) system is a modern initiative in handling traffic violation cases committed by the police. This system uses technology to detect, record and take action against traffic violations electronically. Electronic Traffic Law Enforcement (ETLE) is a traffic law enforcement system that uses CCTV camera technology to detect and record traffic violations automatically. ETLE (Electronic Traffic Law Enforcement) is a modern system that utilizes electronic technology to carry out traffic supervision and law enforcement. This research will discuss the Implementation of Electronic Traffic Law Enforcement (ETLE) at the Polda Metro Jaya Traffic Directorate and the Obstacles to the Implementation of Electronic Traffic Law Enforcement (ETLE) at the Metro Jaya Police Traffic Directorate. The legal research method used is a normative juridical legal research method supported by empirical data. Using a statutory approach and a conceptual approach. obtained from primary, secondary and tertiary legal material sources. Implementation of Electronic Traffic Law Enforcement (ETLE) at the Traffic Directorate of Polda Metro Jaya, namely Installation of CCTV Cameras, Data Integration, Confirmation Letters, Action against Violations and Payment of Fines. Obstacles in the Implementation of Electronic Traffic Law Enforcement (ETLE) at the Traffic Directorate of Polda Metro Jaya are Lack of Facilities and Infrastructure, Data Incompatibility, Lack of Socialization to the Community, Limited Personnel for Supervising Electronic Traffic Law Enforcement (ETLE) and Public Awareness in Low Traffic.